Arnold O. Beckman Oxygen Analyzer - Kassler Studios (1965)
It is unclear how this model of oxygen analyzer relates to the instrument invented by Linus Pauling (and produced by Beckman) during World War II.
Keywords: Scientific apparatus and instruments; Oxygen--Analysis; Beckman Instruments, Inc.